SOCIAL MEDIA IN PUBLIC DOMAIN - R, Revathy; K, Sreena (International Journal of Psychosocial Rehabilitation, 2020)
The public sphere plays a vital role in shaping a society. The places where people of region meet at a time called public sphere. People uses to discuss about certain things like gossips, politics, film and news too. After emergence in social media in the 21st century, social media began to serve the functions similar to the traditional public spheres like teashops. It also helps administration. The term citizen journalism also came after the popularization of social media in the decade of 2010-19.it also became a space for advertisements, film, and political promotions. Thus social media became an integral part of human life.